FRI0144 JOINT-SPECIFIC RESPONSES TO TOFACITINIB AND ADALIMUMAB IN RHEUMATOID ARTHRITIS: A POST HOC ANALYSIS OF DATA FROM ORAL STANDARD AND ORAL STRATEGY. (June 2019) - Ciurea, Adrian; Distler, Oliver; Killeen, Tim; Akylbekova, Ermeg; Kwok, Kenneth; Wang, Lisy; Ospelt, Caroline; Frank-Bertoncelj, Mojca
Abstract : Background: Inflammatory arthritides affect joints variably despite systemic inflammatory cues. Anatomical site-specific differences have been seen in the transcriptome and function of synovial fibroblasts from different joints, 1 including evidence that some joints in rheumatoid arthritis (RA) show differential methylation of genes encoding biological pathways, such as interleukin 6 signalling via the JAK-STAT pathway. 2 Whether such site-specific JAK-STAT sensitivity translates into joint-specific responses to therapeutic JAK inhibition is unknown. Tofacitinib is an oral JAK inhibitor for the treatment of RA. Objectives: To explore joint-specific responses to tofacitinib and adalimumab (ADA) in RA clinical trials. Methods: This was a post hoc analysis of 3-, 6- and 12-month data from the active treatment arms of Phase (P)3 study, ORAL Standard (NCT00853385 ; n=609) and P3b/4 study, ORAL Strategy (NCT02187055 ; n=1152) in patients with active RA refractory to methotrexate (MTX). Both studies included tofacitinib 5 mg BID + MTX and ADA (40 mg SC q2w) + MTX treatment arms. ORAL Standard also included a tofacitinib 10 mg BID + MTX treatment arm and ORAL Strategy, a tofacitinib 5 mg BID treatment arm. A paired joint pathology score (PJPS), a combination of bilateral tender/swollen joint counts ranging from 0 (neither side swollen/tender) to 4 (both sides swollen/tender) was calculated. Data for 33 (ORAL Standard) and 14 (ORAL Strategy) joint pairs were available. The percentage change from baseline (%Δ) in PJPS for each joint was presented in a heat map to visualise responses. To show tofacitinib-specific effects at each joint, difference in mean PJPS for each tofacitinib regimen at 3 months minus the respective ADA + MTX group was calculated. Results: Across all treatment arms of both studies, baseline joint involvement ranged from 15.7% (5th distal interphalangeal joint of the hand) to 93.3% (wrist). All joints showed a treatment response, with%ΔPJPS ranging from –36 to –94% (Figure). The heat map showed lower response rates in the wrist and knee vs most other joints in both studies persisting to 12 months, regardless of treatment arm. Similarly, in ORAL Standard, the ankle (not assessed in ORAL Strategy) showed a lower response vs most other joints. Tofacitinib-specific responses vs ADA + MTX (not shown) were seen (mean differences in PJPS ranged from –0.4 to 0.2) with no clear pattern in the combination therapy groups. In the tofacitinib 5 mg BID arm of ORAL Strategy, a pattern was observed in the metacarpophalangeal (MCP) joints, with tofacitinib responsiveness vs ADA + MTX increasing progressively (mean difference in PJPS increased from 0.16 in MCP1 to –0.08 in MCP5). Conclusion: There is variation in the responsiveness of RA joints to tofacitinib ± MTX and ADA + MTX, with the wrist, knee and ankle responding less well vs other joints, irrespective of treatment mode of action. Concomitant MTX use in most treatment arms may mask joint-specific actions of tofacitinib and ADA. Observed responsiveness to tofacitinib monotherapy vs ADA + MTX increased from MCP1–5, which may be tentative evidence of differential sensitivity to JAK inhibition across embryologically imprinted functional genetic gradients. Further analyses of the monotherapy arms of randomised trials may yield additional evidence of joint-specific responsiveness, and provide a basis for personalised RA treatment. References: [1] Frank-Bertoncelj M, et al. Nat Commun 2017; 8: 14852. [2] Ai R, et al. Nat Commun 2016; 7: 11849. Acknowledgement: Study sponsored by Pfizer Inc. Medical writing support was provided by Kirsten Woollcott of CMC Connect and funded by Pfizer Inc. Disclosure of Interests: Adrian Ciurea Consultant for: AbbVie, Celgene, Janssen-Cilag, MSD, Eli Lilly, Novartis, Pfizer, UCB, Speakers bureau: Abbvie, Celgene, Janssen-Cilag, MSD, Eli Lilly, Novartis, Pfizer, UCB, Oliver Distler Grant/research support from: Prof. Distler received research funding from Actelion, Bayer, Boehringer Ingelheim and Mitsubishi Tanabe to investigate potential treatments of scleroderma and its complications, Consultant for: Prof. Distler has/had consultancy relationship within the last 3 years with Actelion, AnaMar, Bayer, Boehringer Ingelheim, ChemomAb, espeRare foundation, Genentech/Roche, GSK, Inventiva, Italfarmaco, iQvia, Lilly, medac, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Novartis, Pfizer, Sanofi, Serodapharm and UCB in the area of potential treatments of scleroderma and its complications. In addition, he had/has consultancy relationship within the last 3 years with A. Menarini, Amgen, Abbvie, GSK, Mepha, MSD, Pfizer and UCB in the field of arthritides and related disorders, Tim Killeen Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Ermeg Akylbekova Employee of: E Akylbekova is an employee of IQVIA, which is a paid contractor to Pfizer Inc, Kenneth Kwok Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Lisy Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Caroline Ospelt: None declared, Mojca Frank-Bertoncelj Grant/research support from: AbbVie